Soft tissue augmentation - Alam, Murad; Carruthers, Alastair; Carruthers, Jean (Edinburgh : Elsevier, 2018)
Introduction / Jean Carruthers, Alastair Carruthers -- Fillers / Richard G. Glogau -- Facial attractiveness and the central role of volume / Greg J. Goodman -- NASHA family / Rhods S. Narins, Kavita Mariwalla -- Juve? derm family / Shannon Humphrey, Rebecca Fitzgerald -- Belotero and Teosyal / Berthold J. Rzany -- Radiesse and radiesse with lidocaine / Renee C. Sheinin, Bassel H. Mahmoud, David M. Ozog -- Poly - l - Lactic acid / Katie Beleznay, Shannon Humphrey, Rebecca Fitzgerald -- Emervel family / Gary D. Monheit, Berthold Rzany -- Safe fat transplantation / Kyle M. Coleman, William P. Coleman III -- Introduction to permanent fillers / Shilpi Khetarpal, Jeffrey S. Dover -- Liquid injectable silicone / Derek H. Jones, Jeanette M. Black, Harold J. Brody -- Bellafill / Neil S. Sadick -- Forehead reflation / Kavita Mariwalla, Marguerite Germain -- Temple reflation / Derek Jones, Bhushan Hardas, Diane K. Murphy -- Three-dimensional reflation of the glabella and adjacent forehead / Jean Carruthers, Alastair Carruthers -- Volumetric treatment of the brows / Val Lambros -- Infraorbital hollow and nasojugal fold / Shannon Humphrey, Steven Fagien -- Midface / Ada R. Trinade de Almeida, Andre? Vieira Braz -- Nose / Kyle Koo-Il Seo -- Perioral and mandibular filling / Jean Carruthers, Ada R. Trindade de Almeida -- Lip augmentation / Isabela Tollini Jones, Sabrina Guillen Fabi, Jean Carruthers -- Soft tissue augmentation of the hands / Heidi A. Waldorf, Jason J. Emer -- Neck and chest / Monique Vanaman Wilson, Sabrina Guillen Fabi, Steven H. Dayan -- Buttocks / Ada R. Trindade de Almeida, Raul Alberto Banegas -- Earlobe rejuvenation / Laurel Naversen Geraghty -- Tower technique of filler injection / Gerhard Sattler, Sonja Sattler, Birgit Wo? rle -- Vascular compromise / Katie Beleznay, Derek Jones -- Complications of temporary fillers / Joanna G. Bolton, Sabrina Guillen Fabi -- Complications of permanent fillers / Shilpi Khetarpal, Jeffrey S. Dover -- Reverserd / Gabriela Casabona, Jose Raul Montes -- Combinations / Omer brahim, Adele Haimovic, Jeffrey S. Dover -- Legal aspects of soft tissue filler treatments / Mathew M. Avram -- Pretreatment and posttreatment photography / Kevin C. Smith.
Includes bibliographical references and index.
Keywords: Collagen; Cosmetic Techniques; Face